Self-Regulation and Achievement Motivation of Football Athletes in Tanah Karo - Pinem, Harmonis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Basically, everyone has a need for achievement. One of them is like an athlete who pursues certain sports must have the desire to achieve achievements or achieve success. Self-regulation provides an important role in supporting individual achievement, achievement motivation cannot work without self-regulation to take action, especially in sports (Balk & Englert, 2020). So, it can be said that self-regulation and achievement motivation are related. Thus, the purpose of this study isto determine the relationship between self-regulation and achievement motivation of soccer athletes in Tanah Karo.The method used is quantitative with a correlational design. A total of 30 athletes who participated in the study used the accidential sampling technique. Research measurement using The Self-Regulation Questionnaire (= 0.942) and Sport Orientation Questionnaire (= 0.909). The research data analysis method uses the correlation test from Karl Pearson. The results showed that there was no positive relationship between self-regulation and achievement motivation in soccer athletes (r = 0.071 and sig. = 0.355). This indicates thatself-regulation is not one of the factors related to the increased achievement motivation of soccer athletes in Tanah Karo. In other words, self-regulation will not always contribute or fully influence the achievement motivation of athletes, especially soccer athletes in Tanah Karo.